Screening and Characterization of Chitinolytic Bacteria from Shrimp Waste - Batubara, Nikmah Ridha; Suryanto, Dwi; Munir, Erman; Rahmiati, Rahmiati (Universitas Labuhanbatu, 2022)
Shrimp waste is a perishable material. The degradation process is carried out by decaying microbes by producing degrading enzymes. The presence of chitin content in shrimp waste causes the emergence of chitinase enzyme-producing bacteria. Chitin is a linear homopolymer composed of N-acetyl-D-glucosamine monomers with -(1,4) glycosidic bonds. Chitin has unique properties, namely; biodegradable, biocompatible and non-toxic. This causes chitin and its derivatives to be widely used in various industrial and biomedical applications so that chitin and its derivatives have great economic value. There were 10 isolates of chitinolytic bacteria from shrimp waste with varying morphological characteristics. The ten bacterial isolates were NR02, NR03, NR04, NR05, NR06, NR07, NR08, NR09, NR10, NR11 and PU01. Chitinolytic index CI value > 2 was produced by 4 bacterial isolates, namely; NR02, NR07, NR09 and PU01. The lowest IK value was generated by NR08 with a value of 0.01. The chitinolytic bacteria obtained have different characters and it is very likely that they come from different types